Acupuncture Needling, Electroacupuncture, and Fire Needling Improve Imiquimod-Induced Psoriasis-Like Skin Lesions through Reducing Local Inflammatory Responses. (29th July 2019) - Wang, Yan; Fu, Yuanbo; Zhang, Lu; Fu, Jing; Li, Bin; Zhao, Luopeng; Di, Tingting; Meng, Yujiao; Li, Ningfei; Guo, Jianning; Li, Ping; Zhao, Jingxia
Abstract : Psoriasis is a common autoimmune disease. Acupuncture-related techniques have been widely used to treat psoriasis since its ability to engage neuronal function, the immune system, and other systems is well documented. This study aimed to investigate and compare the effects of three common acupuncture-related techniques in psoriasis-like skin inflammatory responses and explore the possible involved mechanisms. Imiquimod (IMQ)-induced psoriasis-like mice were treated with acupuncture needling, electroacupuncture, or fire acupuncture. Methotrexate (MTX) was applied as a positive control. Scoring by the psoriasis area and severity index (PASI) evaluated skin lesion changes. Keratinocyte proliferation and inflammatory cell infiltration were investigated using pathological staining. The secretion levels of inflammatory cytokines were detected by enzyme-linked immunosorbent assay. The expression levels of neuropeptides were assessed by Western immunoblotting. We found that acupuncture needling, electroacupuncture, and fire acupuncture all ameliorated skin lesions, reduced epidermal thickness, inhibited keratinocyte proliferation, and reduced CD3 + T cell infiltration. The aforementioned acupuncture techniques also decreased inflammatory cytokine secretion, including IL-1 β, IL-17A, and IL-23p40. Among them, electroacupuncture showed the best curative effects. Additionally, electroacupuncture downregulated the expression levels of Neurokinin A (NKA), which was positively associated with decreased inflammatory cytokine levels in local lesions. In conclusion, acupuncture needling, electroacupuncture, and fire acupuncture alleviated IMQ-induced psoriasis-like lesions. By contrast, electroacupuncture was more beneficial in reducing the inflammatory response, which might be related to locally dampened neuropeptide levels. Observations support the therapeutic effect of acupuncture for psoriasis and indicate a neuromodulatory mechanism in treating psoriasis by electroacupuncture.